2011
DOI: 10.1108/13673271111179352
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge‐based dynamic capabilities and innovation in networked environments

Abstract: PurposeThe purpose of this paper is to clarify the concept of dynamic capabilities from the knowledge‐based perspective and investigate the mechanisms of dynamic capabilities on innovation performance in networked environments.Design/methodology/approachThis paper designed a seven‐point Likert questionnaire measuring the dynamic capabilities, innovation performance and network embeddedness and a sample of 218 Chinese manufacturing firms were surveyed. Structural equation modeling method was used to statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
380
1
20

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(415 citation statements)
references
References 46 publications
14
380
1
20
Order By: Relevance
“…Many other researchers have used a similar approach to determine the effect of the KMC process on organizational performance (Wu & Chen, 2014;Tseng & Lee, 2014;Tseng, 2014;Gharakhani and Mousakhani, 2012;Chen & Fong, 2012), and the effect of the KMC process on innovation performance (Zheng et al, 2011).…”
Section: Knowledge Management Capabilitiesmentioning
confidence: 99%
“…Many other researchers have used a similar approach to determine the effect of the KMC process on organizational performance (Wu & Chen, 2014;Tseng & Lee, 2014;Tseng, 2014;Gharakhani and Mousakhani, 2012;Chen & Fong, 2012), and the effect of the KMC process on innovation performance (Zheng et al, 2011).…”
Section: Knowledge Management Capabilitiesmentioning
confidence: 99%
“…To sum up, capabilities in general, have been considered as the antecedents for good performance (Zheng et al 2011). Since innovation is one of the aspects that organizations perform to achieve many organizational aims, it can be argued that innovation capabilities are positively related to innovation performance (Lau et al 2010).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Knowledge management capabilities can also be the antecedent of innovation in an organization. Suli et al (2011) found that there is a significant relationship between knowledge-based dynamic capabilities and innovation performance. In a dynamic market situation, companies must be skilled at utilizing internal and external resources to cope with the ever-changing environment.…”
mentioning
confidence: 98%
“…In line with the above discussion, this paper aims to investigate the relationship between knowledge management capabilities and product innovation, also its impact on marketing performance. As a basis for Advances in Economics, Business and Management Research,volume 40 fostering the theories and developing hypotheses, some of the earlier researchers have been adopted, such as Annette M. Mills, et al (2011);Suli Zheng, et al (2011); Chia-Nan Chiu and Huei-Huang Chen (2016).…”
mentioning
confidence: 99%